Dynamics of coastal aquaculture ponds in Vietnam from 1990 to 2015 using Landsat data. Issue 1 (May 2020) - Zhe, Sun; Juhua, Luo; Jingzhicheng, Yang; Li, Zhang
Abstract: It is important to know coastal aquaculture distribution and dynamics for aquaculture sustainability and offshore ocean protection in coastal countries. Vietnam is one of the largest in Asia in aquaculture yield, and thus it is of great significance to map spatial-temporal changes of costal aquaculture for sustainable aquaculture and offshore environment protection in Vietnam. In this study, based on Landsat images from 1990 to 2015, we used object-oriented and decision trees to extract coastal aquaculture ponds, and then analyzed the spatial and temporal distribution and evolution of coastal aquaculture area in Vietnam. The results showed that: 1) the method proposed could effectively extract coastal aquaculture ponds with an overall accuracy of 86%; 2) Vietnam's coastal aquaculture ponds were unevenly distributed and greatly different, and mainly distributed in the Mekong River Delta and Red River Delta, accounting for about 87%; 3) the development of Vietnam's coastal aquaculture ponds can be divided into two main stages, including rapid growth stage before 2010 and slow growth after 2010. This study can provide support for making aquaculture policy and coastal environment protection in Vietnam.